Effects of Tumor-Derived Exosome Programmed Death Ligand 1 on Tumor Immunity and Clinical Applications - Shao, Bo; Dang, Qin; Chen, Zhuang; Chen, Chen; Zhou, Quanbo; Qiao, Bingbing; Liu, Jinbo; Hu, Shengyun; Wang, Guixian; Yuan, Weitang; Sun, Zhenqiang (Frontiers in Cell and Developmental Biology, 2021)
Programmed death ligand 1 (PD-L1) is a typical immune surface protein that binds to programmed cell death 1 (PD-1) on T cells through its extracellular domain. Subsequently, T cell activity is inhibited, and tumor immune tolerance is enhanced. Anti-PD-1/PD-L1 immune checkpoint therapy blocks the combination of PD-1/PD-L1 and rejuvenates depleted T cells, thereby inhibiting tumor growth. Exosomes are biologically active lipid bilayer nanovesicles secreted by various cell types, which mediate signal communication between cells. Studies have shown that PD-L1 can not only be expressed on the surface of tumor cells, immune cells, and other cells in the tumor microenvironment, but also be released from tumor cells and exist in an extracellular form. In particular, exosome PD-L1 plays an unfavorable role in tumor immunosuppression. The immunomodulatory effect of exosome PD-L1 and its potential in fluid diagnosis have attracted our attention. This review aims to summarize the available evidence regarding the biological characteristics of exosome PD-L1 in tumor immunity, with a particular focus on the mechanisms in different cancers and clinical prospects. In addition, we also summarized the current possible and effective detection methods for exosome PD-L1 and proposed that exosome PD-L1 has the potential to become a target for overcoming anti-PD-1/PD-L1 antibody treatment resistance.